Barriers to Implementation of Lean Accounting in Manufacturing Companies - Roya Darabi; Razieh Moradi; Usef Toomari (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
According to previous research and foreign studies, there are various barriers to implementation of lean accounting and this research aimed at studying these barriers. The data was collected using a questionnaire. This research is applied in its purpose, and a field study regarding its methodology. Student's t-Tests method was used to test hypotheses. The results show that cultural, technical, organizational, and economic factors were barriers to implementation of lean accounting. Moreover, regarding the four groups of factors, technical factors had the highest degree of impeding and economic factors the lowest.